Ranibizumab treatment improves diabetic macular oedema without influencing retinal oximetry parameters. Issue 8 (24th May 2019) - Takasago, Yukari; Fujita, Tomoyoshi; Nakano, Yuki; Osaka, Rie; Miyake, Masahiro; Muraoka, Yuki; Tsujikawa, Akitaka
Abstract: Purpose: To evaluate the effect of ranibizumab on retinal oximetry in eyes with diabetic macular oedema (DME). Methods: In this prospective interventional study, 30 eyes (30 patients) with DME were treated with three‐monthly intravitreal ranibizumab injections, followed by pro re nata administration for 12 months. Retinal oximetry was performed using an Oxymap T1. Results: The mean number of injections was 6.6 ± 2.5. No adverse event was observed throughout the study period. Ranibizumab treatments for 12 months improved the macular oedema (p = 0.002) and achieved a recovery of visual acuity (VA; p = 0.011). However, oxygen saturation levels in the major retinal blood vessels, either the arteries or the veins, remained unchanged during the observational period. Arterial oxygen saturation was 100.3 ± 9.4% before treatment and 100.9 ± 10.7% (p = 0.698) at 6 months. Venous oxygen saturation was 56.4 ± 8.9% before treatment and 55.6 ± 8.6% (p = 0.529) at 6 months. In addition, there were no significant changes in diameters of the major retinal arteries and veins. Greater improvement of VA at 12 months was correlated with a smaller number of ranibizumab injections ( r  = 0.459, p = 0.011). The number of ranibizumab injections during these 12 months correlated with an increased baseline central retinal thickness ( r  = 0.385, p = 0.035). Conclusion: Ranibizumab treatments for DME improved the macular oedema and achieved VA recovery, but no changes were noted in the retinal oxygen saturation.